A combined approach for single-cell mRNA and intracellular protein expression analysis - Johan Reimegård (Nature Portfolio, 2021)
Here, the authors present SPARC, a scalable approach for simultaneously measuring mRNA expression levels and targeted intracellular protein levels in single cells. They use SPARC to measure dynamic expression changes in human cells during neuronal differentiation and show that mRNA levels are poor predictors of protein abundances and activity in individual cells, indicating that the measurements are complementary.